Use of ChatGPT and Its Impact on Students’ Learning Experience Among the Students from Higher Education Institutions in Pokhara - Ranabhat, Deepesh; Sapkota, Pradeep; Malla, Subash; Shrestha, Kusum; Ranabhat, Mala (Journal of Interdisciplinary Studies, 2024)
The use of Artificial Intelligence (AI) tools like ChatGPT has seen rapid adoption among students for tasks such as writing, summarizing, and research in recent years. This study aims to investigate the factors influencing ChatGPT usage and its impact on students’ learning outcomes, focusing on higher education institutions (HEIs) in Pokhara, Nepal. A quantitative research approach was employed, utilizing descriptive and analytical designs. Data were collected from 184 valid responses through a structured questionnaire and analyzed using statistical tools, including mean analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM). The study explored constructs such as reliability, accuracy, security, privacy, usefulness, and convenience. The findings reveal that convenience and reliability significantly influence the use of ChatGPT, while accuracy, security, and privacy do not show a statistically significant effect. Moreover, the study found a strong positive relationship between the use of ChatGPT and its impact on learning, indicating that increased usage leads to enhanced learning experiences, access to educational resources, and improved academic productivity. This study highlights that ease of use and reliability are key factors driving ChatGPT’s adoption in educational settings, providing valuable insights for educators and policymakers to optimize AI tools for effective learning.